(x - 3^2)^3 . (x-3^2) = (10^2)^2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: =25(15+45*3)
=25*150
=3750
b: \(=-10\left(25+75-50\right)=-10\cdot50=-500\)
c: =>3^x-2=27
=>x-2=3
=>x=5
d: =>2x-5=-4
=>2x=1
=>x=1/2
e: =>2(x-1)^2=32
=>(x-1)^2=16
=>x-1=4 hoặc x-1=-4
=>x=-3 hoặc x=5
f: =>25(x+3)=75
=>x+3=3
=>x=0
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=5x^2-3x-x^3+x^2+x^3-62x-10+3x\\ A=6x^2-62x-10\\ B=x^3+x^2+x-x^3-x^2-x+5=5\\ C=3x^2y-15xy^2+15xy^2-10y^3+10y^2-3x^2y-4=-4\)
b: Ta có: \(B=x\left(x^2+x+1\right)-x^2\left(x+1\right)-x+5\)
\(=x^3+x^2+x-x^3-x^2-x+5\)
=5
![](https://rs.olm.vn/images/avt/0.png?1311)
1) 2(x + 5) + 3(x + 7) = 41
2x + 10 + 3x + 21 = 41
5x + 31 = 41
5x = 10
x = 2
6) 7(x - 1) + 5(3 - x) = 11x - 10
7x - 7 + 15 - 5x = 11x - 10
2x + 8 = 11x - 10
-9x = -18
x = 2
2) 5(x + 6) + 2(x - 3) = 38
5x + 30 + 2x - 6 = 38
7x + 24 = 38
7x = 14
x = 2
7) 4(2 + x) + 3(x - 2) = 12
8 + 4x + 3x - 6 = 12
7x + 2 = 12
7x = 10
x = 10/7
3) 7(5 + x) + 2(x - 10) = 15
35 + 7x + 2x - 20 = 15
9x + 15 = 15
9x = 0
x = 0
8) 5(2 + x) + 4(3 - x) = 10x - 15
10 + 5x + 12 - 4x = 10x - 15
x + 22 = 10x - 15
9x = 37
x = 37/9
4) 3(x + 4) + (8 - 2x) = 22
3x + 12 + 8 - 2x = 22
x + 20 = 22
x = 2
9) 7(x - 2) + 5(3 - x) = 11x - 6
7x - 14 + 15 - 5x = 11x - 6
2x + 1 = 11x - 6
-9x = -7
x = 7/9
5) 4(x + 5) + 3(7 - x) = 49
4x + 20 + 21 - 3x = 49
x + 41 = 49
x = 8
10) 5(3 - x) + 5(x + 4) = 6 + 4x
15 - 5x + 5x + 20 = 6 + 4x
35 = 6 + 4x
4x = 29
x = 29/4
1) 2(x + 5) + 3(x + 7) = 41
2x + 10 + 3x + 21 = 41
5x + 31 = 41
5x = 41 - 31
5x = 10
x = 10 : 5
x = 2
2) 5(x + 6) + 2(x - 3) = 38
5x + 30 + 2x - 6 = 38
7x + 24 = 38
7x = 38 - 24
7x = 14
x = 14 : 7
x = 2
3) 7(5 + x) + 2(x - 10) = 15
35 + 7x + 2x - 20 = 15
9x + 15 = 15
9x = 15 - 15
9x = 0
x = 0
4) 3(x + 4) + (8 - 2x) = 22
3x + 12 + 8 - 2x = 22
x + 20 = 22
x = 22 - 20
x = 2
5) 4(x + 5) + 3(7 - x) = 49
4x + 20 + 21 - 3x = 49
x + 41 = 49
x = 49 - 41
x = 8
6) 7(x - 1) + 5(3 - x) = 11x - 10
7x - 7 + 15 - 5x = 11x - 10
2x - 11x + 8 = -10
-9x = -10 - 8
-9x = -18
x = -18 : (-9)
x = 2
7) 4(2 + x) + 3(x - 2) = 12
8 + 4x + 3x - 6 = 12
7x + 2 = 12
7x = 12 - 2
7x = 10
x = 10/7
8) 5(2 + x) + 4(3 - x) = 10x - 15
10 + 5x + 12 - 4x = 10x - 15
10x - 15 = x + 22
10x - x = 22 + 15
9x = 37
x = 37/9
9) 7(x - 2) + 5(3 - x) = 11x - 6
7x - 14 + 15 - 5x = 11x - 6
11x - 6 = 2x + 1
11x - 2x = 1 + 6
9x = 7
x = 7/9
10) 5(3 - x) + 5(x + 4) = 6 + 4x
15 - 5x + 5x + 20 = 6 + 4x
6 + 4x = 35
4x = 35 - 6
4x = 29
x = 29/4
![](https://rs.olm.vn/images/avt/0.png?1311)
1; 5.22 + (\(x\) + 3) = 52
5.4 + (\(x\) + 3) = 25
20 + (\(x\) + 3) = 25
\(x\) + 3 = 25 - 20
\(x+3\) = 5
\(x\) = 5 - 3
\(x\) = 2
Vậy \(x=2\)
2; 23 + (\(x\) - 32) = 53 - 43
8 + (\(x\) - 9) = 125 - 64
8 + (\(x\) - 9) = 61
\(x\) - 9 = 61 - 8
\(x\) - 9 = 53
\(x\) = 53 + 9
\(x\) = 62
Vậy \(x\) = 62
![](https://rs.olm.vn/images/avt/0.png?1311)
a: =16-2+91=14+91=105
b: =9*5+8*10-27=45+53=98
c: =32+65-3*8=8+65=73
d; \(=5^3-10^2=125-100=25\)
e: \(=4^2-3^2+1=8\)
f: =9*16-16*8-8+16*4
=16(9-8+4)-8
=16*5-8
=72
a) \(2^4-50:25+13\cdot7\)
\(=2^4-2+91\)
\(=16-2+91\)
\(=14+91\)
\(=105\)
b) \(3^2\cdot5+2^3\cdot10-3^4:3\)
\(=9\cdot5+8\cdot10-3^3\)
\(=45+80-27\)
\(=98\)
c) \(2^5+5\cdot13-3\cdot2^3\)
\(=32+65-3\cdot8\)
\(=32+65-24\)
\(=73\)
d) \(5^{13}:5^{10}-5^2\cdot2^2\)
\(=5^{13-10}-\left(5\cdot2\right)^2\)
\(=5^3-10^2\)
\(=125-100\)
\(=25\)
e) \(4^5:4^3-3^9:3^7+5^0\)
\(=4^{5-3}-3^{9-7}+1\)
\(=4^2-3^2+1\)
\(=16-9+1\)
\(=8\)
f) \(3^2\cdot2^4-2^3\cdot4^2-2^3\cdot5^0+4^2\cdot2^2\)
\(=3^2\cdot4^2-2^3\cdot4^2-2^3\cdot1+4^2\cdot2^2\)
\(=4^2\cdot\left(3^2-2^3+2^2\right)-2^3\)
\(=4^2\cdot\left(9-8+4\right)-8\)
\(=16\cdot5-8\)
\(=72\)